New therapeutic opportunities from dissecting the pre-B leukemia bone marrow microenvironment. Issue 11 (November 2018) - Cheung, Laurence; Tickner, Jennifer; Hughes, Anastasia; Skut, Patrycja; Howlett, Meegan; Foley, Bree; Oommen, Joyce; Wells, Julia; He, Bo; Singh, Sajla; Chua, Grace-Alyssa; Ford, Jette; et al.
Abstract The microenvironments of leukemia and cancer are critical for multiple stages of malignancies, and they are an attractive therapeutic target. While skeletal abnormalities are commonly seen in children with acute lymphoblastic leukemia (ALL) prior to initiating osteotoxic therapy, little is known about the alterations to the bone marrow microenvironment during leukemogenesis. Therefore, in this study, we focused on the development of precursor-B cell ALL (pre-B ALL) in an immunocompetent BCR-ABL1+ model. Here we show that hematopoiesis was perturbed, B lymphopoiesis was impaired, collagen production was reduced, and the number of osteoblastic cells was decreased in the bone marrow microenvironment. As previously found in children with ALL, the leukemia-bearing mice exhibited severe bone loss during leukemogenesis. Leukemia cells produced high levels of receptor activator of nuclear factor κB ligand (RANKL), sufficient to cause osteoclast-mediated bone resorption. In vivo administration of zoledronic acid rescued leukemia-induced bone loss, reduced disease burden and prolonged survival in leukemia-bearing mice. Taken together, we provide evidence that targeting leukemia-induced bone loss is a therapeutic strategy for pre-B ALL.